Overview of Animal Manure Management for Beef, Pig, and Poultry Farms in France - Loyon, Laurence (Frontiers in Sustainable Food Systems, 2018)
Livestock manure management is the central issue for many environmental policies relating to water and air quality. However, there is little published data on the methods used in those countries affected by pollution from the livestock sector. This paper brings together the available data relating to manure management in France, specifically for pig, cattle and poultry production. An overview of livestock production and legislation is presented using data from the 2010 Agricultural Census, livestock farm surveys carried out in 2008 and other supporting documents relating to manure treatment (professional surveys, expert reports and technical publications). Cattle, pig, and poultry livestock produce around 120 million tons of manure per year not including those on pasture. This figure is made up from 60.6% solid manure, 38.8% livestock slurry (effluent) and a relatively small amount of poultry droppings. Solid manure is mainly stored in temporary field heaps. In the case of manure storage on the farm, the capacity varies from 45 days to 7.5 months depending on farm size and type of animals, time spent outside the buildings and the geographical location. Covered storage (whether rigid or natural crust) accounts for 17% of stored pig slurry, 45% of cattle slurry, and 39% of poultry slurry. Covered storage of solid manure is rarely used on pig or cattle farms whereas 27% of the solid poultry manure (including poultry droppings) is held in covered storage areas. Treatment applies to 13.6 million tons of the manure produced, mainly by methods based on composting or aerobic treatment. Nitrogen applied as slurry is mostly spread on the soil surface using splash plate tankers (83% in the case of cattle slurry, 63% for pig slurry, and 66% for poultry slurry). Incorporation within 24 h of the nitrogen spread on the soil concerns 28% of cattle, 44% of pig, and 56% of poultry manure. The most common method of manure management is storage (in building and pit) and spreading. The treatment of manure and the use of specific techniques to reduce gaseous emissions (such as frequent manure removal from buildings, storage covers, or injection) are not widely reported.